Relationship Between Wudu Practice Frequency and Academic Achievement Among Elementary School Students at SD Aisyiyah Saubari Bening Hati Semarang - Muslimah Muslimah; Rochman Basuki; Wijayanti Fuad; Firda Khoirun Nisa (Universitas Islam Sultan Agung, 2026)
Academic performance in primary education is shaped not only by intellectual ability but also by behavioral patterns and daily routines that support learning readiness. Regular ablution (wudu), as part of Islamic practice, may be associated with discipline, emotional balance, and attentional control factors closely related to effective learning. This study investigated whether the frequency of wudu practice is associated with academic achievement among students at SD Aisyiyah Saubari Bening Hati Semarang. An analytic cross-sectional study was conducted involving 54 students from grades IV to VI. Frequency of wudu was assessed through a structured questionnaire, while academic achievement was obtained from documented report card averages. Pearson correlation analysis demonstrated a statistically significant moderate association (r = 0.420; p = 0.002). Students who reported more consistent wudu practice tended to demonstrate higher academic scores within this study sample. Although the findings indicate a meaningful association, the study design does not permit causal interpretation. These results highlight the potential contribution of structured spiritual habits to students’ academic engagement and performance, warranting further longitudinal investigation.